Reptiles (Encyclopaedia Britannica Educational Corp., 1954)
Introduces the five orders of reptiles remaining on earth: lizards, turtles, tuataras, crocodilians and serpents. Describes the physical characteristics of these animals, their reproduction processes, feeding habits, and special habitats. Points out some of the ways in which reptiles are useful to man.